New age issues in medical ethics - time to address - Yadav, Juhi; Gupta, Shalini (International Journal Of Community Medicine And Public Health, 2021)
Medical technology advancements and understanding along with constricted resources in provision of care to the needed, has arised ethical dilemmas. These are associated with the necessity of making decisions dependent on conflicting priorities, in the absence of established polices about the choice of the decision maker and the guiding principles checklist. Varying values and ethical models conflict current code of medical ethics making it inadequate. This article summarises key issues in contemporary medical ethics and a special note of medical negligence.